Effect of Alkaline Activator to Fly Ash Ratio for Geopolymer Stabilized Soil - Abdullah, Muhammad Sofian; Ahmad, Fauziah (EDP Sciences, 2017)
Geopolymer technology have been developed and explored especially in the construction material field. However, lack of research related to geopolymer stabilized soil. In this research, the utilization of geopolymer has been investigated to stabilize the soil including the factors that affecting the geopolymerization process. Unconfined compressive test (UCT) used as indicator to the strength development and hence evaluating the performance of geopolymer stabilized soil. This paper focusing on the effect of fly ash/alkaline activator ratio, Na2SiO3/NaOH ratio and curing time on geopolymer stabilized soil. A various mix design at different fly ash/alkaline activator ratio, Na2SiO3/NaOH ratio were prepared and cured for 7 and 28 days. Molarity and the percentage of geopolymer to soil were fixed at 10 molar and 8 percent respectively. Then, the UCT tests were carried out on 38mm diameter x 76mm height specimens. The highest strength obtained at the fly ash/alkaline activator ratio 2.5 and Na2SiO3/NaOH ratio 2.0 at 28 days curing time.